Geophysical Monitoring of Moisture‐Induced Landslides: A Review. (12th February 2019) - Whiteley, J. S.; Chambers, J. E.; Uhlemann, S.; Wilkinson, P. B.; Kendall, J. M.
Abstract: Geophysical monitoring of landslides can provide insights into spatial and temporal variations of subsurface properties associated with slope failure. Recent improvements in equipment, data analysis, and field operations have led to a significant increase in the use of such techniques in monitoring. Geophysical methods complement intrusive approaches, which sample only a very small proportion of the subsurface, and walk‐over or remotely sensed data, which principally provide information only at the ground surface. In particular, recent studies show that advances in geophysical instrumentation, data processing, modeling, and interpretation in the context of landslide monitoring are significantly improving the characterization of hillslope hydrology and soil and rock hydrology and strength and their dynamics over time. This review appraises the state of the art of geophysical monitoring, as applied to moisture‐induced landslides. Here we focus on technical and practical uses of time‐lapse methods in geophysics applied to monitoring moisture‐induced landslide. The case studies identified in this review show that several geophysical techniques are currently used in the monitoring of subsurface landslide processes. These geophysical contributions to monitoring and predicting the evolution of landslide processes are currently underrealized. Hence, the further integration of multiple‐parametric and geotechnically coupled geophysical monitoring systems has considerable potential. The complementary nature of certain methods to map the distribution of subsurface moisture and elastic moduli will greatly increase the predictive and monitoring capacity of early warning systems in moisture‐induced landslide settings. Key Points: Geophysical monitoring reveals high resolution spatial and temporal information from the subsurface of landslide systems Developments in geophysical monitoring have led to substantial increases in applications to landslides and frequencies of data acquisition Linking geophysical data with geotechnical measurements can monitor hydrological and geomechanical processes in time and space